Behind the QAS counter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Manual for the management of Question-and-Answer Services. CTA, 2001. 132 pp. ISBN 92 9081 2443 CTA number 1043. 20 credit points